(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the prevalence of fungal infection in the patients having nasal polyps at Liaquat University Hospital, Hyderabad. Study Design: Observational and prospective study Place and Duration of Study: This study was conducted in the Department of the ENT of Liaquat University Hospital, Jamshoro/Hyderabad from March 2012 to August 2012. Materials and Methods: Total 50 had selected. All the cases with nasal polyp, both genders and above 18 years of the age were integrated. Routine lab investigations had completed. Radiological examination including the X-ray of paranasal sinuses and CT scan had done to diagnosis sinuses, bony erosion, orbital and intracranial extension. Surgical procedure had done according to the need of the patient. After surgery all the samples separated in 2 places under sterile process. One for histopathology and 2nd in the normal saline had sent for fungal Culture of specimen. Results: Total 50 cases were selected in the study after diagnosis of nasal polyp, mean age of the cases was mean +SD=36.05+7.21 years, male had found in the majority 31/(62.0%). Nasal obstruction was the most common 42/(84.0%) in the clinical presentation. Majority of the cases 26.0% were under went surgical procedure of nasal polypectomy. After done histopathology frequently diagnosis found as Inflammatory polyp 43/(86.0%), while 08/(16.0%) cases were found with fungal infection and 42/(84.0%) were without fungal infection after culture test. Conclusion: In conclusion fungal infection is found most common in the cases having nasal polyps